Generation of ornamental Nile tilapia with distinct gray and black body color pattern by csf1ra mutation - Baoyue Lu; Chenxu Wang; Guangyuan Liang; Mengmeng Xu; Thomas D. Kocher; Lina Sun; Deshou Wang (Aquaculture Reports, 2022)
Nile tilapia (Oreochromis niloticus) is an important species in aquaculture and an excellent model fish for studying teleost color patterns. Colony-stimulating factor 1 receptor a (csf1ra) is critical for xanthophores development and body color formation in zebrafish and guppy. In this study, we established csf1ra mutant lines with two different targets by CRISPR/Cas9 in Nile tilapia. Unlike the wild type fish (WT) with vertical bars, the homozygous mutants showed two different color patterns, either uniformly gray (GT) or gray with black tail (BT). Compared with WT, the mutants had fewer melanophores, a few xanthophores and no erythrophores. Increased numbers of melanophores were observed in the tail of BT mutants. However, the establishment of early embryonic pigment cell precursors and the appearance of melanophores on the body were independent of csf1ra. In contrast, the appearance of xanthophores on the body and the formation of the vertical bar pattern dependent on the late metamorphic melanophores required csf1ra. The deletion of xanthophores and erythrophores caused by csf1ra mutation changed the body color pattern of Nile tilapia. These results demonstrated that csf1ra activity is essential for the development of erythrophores, late developing xanthophores and late metamorphic melanophores. These mutants provided good models for analyzing the genetic basis of tilapia body color pattern formation. Our study may help deepen the understanding of the formation of fish body color pattern, especially for cichlids with vertical bars. In addition, the mutants might be developed as ornamental fish (BT) or new strains for aquaculture.